2021
DOI: 10.5194/acp-21-14371-2021
|View full text |Cite
|
Sign up to set email alerts
|

The outflow of Asian biomass burning carbonaceous aerosol into the upper troposphere and lower stratosphere in spring: radiative effects seen in a global model

Abstract: Abstract. Biomass burning (BB) over Asia is a strong source of carbonaceous aerosols during spring. From ECHAM6–HAMMOZ model simulations and satellite observations, we show that there is an outflow of Asian BB carbonaceous aerosols into the upper troposphere and lower stratosphere (UTLS) (black carbon: 0.1 to 6 ng m−3 and organic carbon: 0.2 to 10 ng m−3) during the spring season. The model simulations show that the greatest transport of BB carbonaceous aerosols into the UTLS occurs from the Indochina and East… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
(92 reference statements)
4
7
0
Order By: Relevance
“…This confirms that the observed increase in AOD Myanmar and central Indian regions has been caused by large amounts of fires. A past study shows that fires emit smoke/carbonaceous aerosols peak in spring over the Myanmar region (Chavan et al, 2021). It will be interesting to observe the vertical structure of fire-emitted smoke.…”
Section: Variability In Fires and Aerosol Loadingmentioning
confidence: 97%
“…This confirms that the observed increase in AOD Myanmar and central Indian regions has been caused by large amounts of fires. A past study shows that fires emit smoke/carbonaceous aerosols peak in spring over the Myanmar region (Chavan et al, 2021). It will be interesting to observe the vertical structure of fire-emitted smoke.…”
Section: Variability In Fires and Aerosol Loadingmentioning
confidence: 97%
“…India has suffered massive forest fires each year due to natural and anthropogenic causes, with the main concentration in the hilly terrains of the western/central Himalayas and the northeastern states. A large number of forest fires from November 2020 to June 2021 were reported in Odisha (51,968), Madhya Pradesh (47,795), Chhattisgarh (38,106), Maharashtra (34,025), Jharkhand (21,713), Uttarakhand (21,497), Andhra Pradesh (19,328), Telangana (18,237), Mizoram (12,864), Assam (10,718), and Manipur (10,475) [67]. Approximately 1300 hectares of forest area burned due to massive forest fires in 2021 in Uttarakhand state [68].…”
Section: Identification Of Forest Firementioning
confidence: 99%
“…Wildfires and biomass burning are among the major important sources of carbonaceous aerosols, greenhouse gases, ozone precursors, trace gases, and particulate pollutant emissions in several regions, including Asia [3][4][5][6][7][8][9][10][11][12][13]. The impacts of forest fires and biomass burning on aerosols, air pollution, and radiative forcing over northern India were well documented in several earlier papers [3,9,[14][15][16][17][18][19][20][21][22][23], and are hence not repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…1d), with increases for BC of 0 %-3 %, OC of 0 %-8.7 %, and sulfate of 0 %-0.2 %, compared to annual means. This peak in emissions in spring is to a large extent driven by springtime agricultural crop burning and biomass burning activity (Chavan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Airborne observations during winter and spring, e.g., the Civil Aircraft for Regular Investigation of the Atmosphere based on an Instrument Container (CARIBIC) in March 1999and January 2001(Papaspiropoulos et al, 2002 and the Indian Ocean Experiment (INDOEX) in February-March 1999, show elevated aerosol amounts near 8-12 km over the Indian Ocean and South Asia (De Reus et al, 2001). Recently, using a set of model simulations, Chavan et al (2021) reported the transport of biomass burning aerosols to the upper troposphere by convection in spring 2013.…”
Section: Introductionmentioning
confidence: 99%